Strategi Coping Stres Pada Penderita Lupus - Cahyaningtyas, Helga; Wisnu Sri Hertinjung,, Wisnu Sri Hertinjung,.S.Psi., M.Psi,Psi (2016)
AbstractThe purpose of this research is to gain an understanding of stress coping strategies with lupus. This study used a qualitative method with informants totaling 6 informants consists of three main informants and informant support 3. Key informants are people with lupus aged teens, early adulthood and middle age. Then the informant is the closest supporters of the main informant who accompanied during the main informant suffered from lupus. Data were obtained by interview and observation. Based on the results of the study indicate that the all the informant experiencing stressful conditions, such as difficulty concentrating, lazy activity, desperate, anxious, angry, silent, closed, self-esteem, decreased memory, denial, fear, weakness and headache Coping conducted informant adolescents and adults showed differences, adolescent informants tend to use emotional focused coping while adult informants did to two coping that is problem focused coping and emotional focused coping. There are factors that affect informants Coping With a factor of education and social support factors that focus on the emotional. Key word : coping, stress, lupus patients